2020
DOI: 10.1017/s1355617720001083
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Demographic Variables in Neuropsychological Research: An Update of O’Bryant et al.’s Trends in the Current Literature

Abstract: Objective: Demographic trends and the globalization of neuropsychology have led to a push toward inclusivity and diversity in neuropsychological research in order to maintain relevance in the healthcare marketplace. However, in a review of neuropsychological journals, O’Bryant et al. found systematic under-reporting of sample characteristics vital for understanding the generalizability of research findings. We sought to update and expand the findings reported by O’Bryant et al. Method: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Prospective standardized collection and reporting of key sociodemographic factors 49 across sites would further help characterize selection factors and improve generalizability of results from large datasets like NACC. Future studies should also consider leveraging transportability methods such as weighting and outcome modeling aimed at generalizing findings to external populations 50–53 . These methods have important assumptions that limit their applicability, but there is some recent work in aging samples 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective standardized collection and reporting of key sociodemographic factors 49 across sites would further help characterize selection factors and improve generalizability of results from large datasets like NACC. Future studies should also consider leveraging transportability methods such as weighting and outcome modeling aimed at generalizing findings to external populations 50–53 . These methods have important assumptions that limit their applicability, but there is some recent work in aging samples 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Each site is per- Future studies should also consider leveraging transportability methods such as weighting and outcome modeling aimed at generalizing findings to external populations. [50][51][52][53] These methods have important assumptions that limit their applicability, but there is some recent work in aging samples. 53 Last, future work evaluating updated recruitment strategies will also want to consider the impact of major historic events on research recruitment and enrollment, like the COVID-19 pandemic.…”
Section: Ta B L Ementioning
confidence: 99%
“…Moreover, we found that the software name or version (or both) used for data processing was reported for only 30.9% (34/110) of the BioMeTs, indicating that the data cannot be reproduced even if the hardware details are known. We also noted key gaps in the descriptive data; most notably, only 41% (41/100) reported the ethnicity or race of participants, which is a persistent problem in clinical research [22,23]. Even among the 46 studies performed in the United States, for which there are clear guidelines for collecting and reporting race and ethnicity [24], 30% (14/46) of the studies did not provide these data.…”
Section: Principal Findingsmentioning
confidence: 99%
“…O’Bryant et al (2004) noted that information on race, ethnicity, native language and acculturation are often not reported in research articles, which likely limits progress in cross-cultural neuropsychology. Medina et al (2021) provided a recent update on these trends, and while reporting of these variables in research papers is slowly improving, greater systematic reporting of these variables is needed. They present specific recommendations by Rad et al (2018) as a possible path forward.…”
Section: Recommendations For Research In Cross-cultural Neuropsychologymentioning
confidence: 99%